Randomized clinical study of electrical impedance tomography-guided chest physiotherapy in difficult-to-wean patients: study protocol - Wang, Hao; Xi, Jianing; Jiang, Hongying (PeerJ, 2025)
Background Diaphragm dysfunction and inadequate chest wall and respiratory muscle function are common in critically ill patients who face difficulties in weaning from mechanical ventilation (MV). This can lead to secretion retention and impaired airway clearance. Chest physiotherapy (CPT) in these patients can help reduce secretion retention. This study protocol outlines an investigation into the feasibility and effectiveness of CPT guided by electrical impedance tomography (EIT) in difficult-to-wean patients on lung function, duration of mechanical ventilation, functional performance, and intensive care unit (ICU) hospitalization expenses. Methods This single-center, single-blind, randomized pilot study employed a parallel-group design. Participants will be randomly assigned to either an intervention group receiving EIT-guided CPT or a control group receiving only experiential CPT Interventions, lasting 20 minutes each, were administered up to twice daily from ICU admission until discharge. The assessments will occur before interventions, after the 14 days, and after the 28 days. Outcome measures will be collected at before and after the intervention, peak expiratory flow, 30-day weaning success rate, maximum inspiratory pressure, diaphragm thickening rate, diaphragmatic excursion, ICU stay duration, and days from baseline to MV removal or Day 30. Adverse events will be documented. Conclusion This study will evaluate the feasibility and effectiveness of EIT-guided CPT versus conventional CPT in difficult-to-wean patients. If successful, this approach could enhance the efficiency of CPT. Trial registration This study was prospectively registered at the National Library of Medicine (https://clinicaltrials.gov/; reference: NCT06677099; Date of registration: 5th November 2024).
Keywords: Mechanical ventilation; Chest physiotherapy; Electrical impedance tomography; Study protocol; Airway clearance; Intensive care